2018
DOI: 10.1101/498451
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Environmental DNA metabarcoding as an effective and rapid tool for fish monitoring in canals:

Abstract: Environmental DNA (eDNA) metabarcoding has revolutionized biomonitoring of aquatic habitats. Man-made canal systems are among the least-studied environments in terms of biodiversity in Britain. Here we focus on a case study along an English canal comparing eDNA metabarcoding with two types of electrofishing techniques (wade-and-reach and boom-boat). In addition to corroborating data obtained by electrofishing, eDNA provided a wider snapshot of fish assemblages.Given the semi-lotic nature of canals, we encourag… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
17
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 19 publications
(10 reference statements)
1
17
0
Order By: Relevance
“…Previous studies have clearly shown that eDNA metabarcoding is a highly sensitive method for the detection of freshwater fish, which outperforms traditional survey techniques in lentic environments (Handley et al, 2019;Hänfling et al, 2016;Li et al, 2019). This study adds to the mounting evidence that this is also true in lotic environments with unregulated (Bylemans et al, 2018; and regulated flows (McDevitt et al, 2019). Despite the underestimation of true species richness in traditional surveys, when compared to eDNA metabarcoding there was a strong positive correlation between both methods, and thus, the relative importance of sites based on species richness for both methods was related.…”
Section: Fish Community Detection In Pumped Catchmentsmentioning
confidence: 52%
See 1 more Smart Citation
“…Previous studies have clearly shown that eDNA metabarcoding is a highly sensitive method for the detection of freshwater fish, which outperforms traditional survey techniques in lentic environments (Handley et al, 2019;Hänfling et al, 2016;Li et al, 2019). This study adds to the mounting evidence that this is also true in lotic environments with unregulated (Bylemans et al, 2018; and regulated flows (McDevitt et al, 2019). Despite the underestimation of true species richness in traditional surveys, when compared to eDNA metabarcoding there was a strong positive correlation between both methods, and thus, the relative importance of sites based on species richness for both methods was related.…”
Section: Fish Community Detection In Pumped Catchmentsmentioning
confidence: 52%
“…Knowledge of the eel distribution and fish community present at these sites is therefore valuable to water managers (Solomon & Wright, 2012), yet due to sampling difficulties the probability of detecting rare and elusive species using traditional methods is lowparticularly in large river systems . Nonetheless, numerous studies in freshwater habitats have demonstrated that environmental DNA (eDNA) monitoring methods can achieve higher detection sensitivity than traditional monitoring techniques (Hänfling et al, 2016;Itakura et al, 2019;McDevitt et al, 2019;Strickland & Roberts, 2018). These molecular monitoring methods are ideal for detecting species with patchy distributions or low abundances, often overlooked by traditional catch methods (Turner et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…During the past decade, environmental DNA (eDNA) emerged as a rapid, reliable and non‐invasive tool for inventorying fish richness (Pawlowski et al ., 2018; Rees et al ., 2014). Tracing eDNA allows a better species detection compared to traditional EF methods in diverse habitats (Bohmann et al ., 2014; McDevitt et al ., 2019; Valentini et al ., 2016), reducing sampling effort and cost (Evans et al ., 2017). Nonetheless, a major constraint of the eDNA method is its limited ability for the quantitative estimation of fish assemblages.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have clearly shown that eDNA metabarcoding is a highly sensitive method for detection of freshwater fish which outperforms traditional survey techniques in lentic environments (Hänfling et al, 2016;Handley et al, 2019;Li et al, 2019). This study adds to the mounting evidence that this is also true in lotic environments with unregulated (Bylemans et al, 2018;Pont et al, 2018) and regulated flows (McDevitt et al, 2019). Despite the underestimation of true species richness in traditional surveys, when compared to eDNA metabarcoding there was a strong positive correlation between both methods, and thus the relative importance of sites based on species richness for both methods were related.…”
Section: Fish Community Detection In Pumped Catchmentsmentioning
confidence: 52%
“…However, numerous studies in freshwater habitats have demonstrated that environmental DNA (eDNA) monitoring methods can achieve higher detection sensitivity than traditional monitoring techniques (Hänfling et al, 2016;Pont et al, 2018;Strickland & Roberts, 2018;Itakura et al, 2019;McDevitt et al, 2019). These molecular monitoring methods are ideal for detecting species with patchy distributions or low abundances, often overlooked by traditional catch methods (Turner et al, 2015).…”
Section: Introductionmentioning
confidence: 99%